Gender and leadership in the Spanish university. A study on the gender gap in university management - López, Mercedes Cuevas; Rosas, Francisco Díaz (Education Policy Analysis Archives, 2015)
As a prior step to knowledge about leadership styles exercised by women in Spanish universities, it is imperative to know what the current situation as far as managerial positions is concerned. In this article, part of a broader study within the Gendercit Project (PIRSES-GA-2012-318960) in which the performance of the managers in different centers of the participating universities is addressed, a descriptive analysis of the current situation of the Spanish public universities is presented. With this purpose, data about the composition of the government teams of each university and each of their respective schools and colleges have been collected. The purpose of this research is to provide a description of the presence of women in two of the most important areas of government of the Spanish public university: education authorities, and the deanship of colleges or polytechnic schools. The information presented has been obtained by analyzing the web pages of each institution between 25 November and 30 January 2015. The indicator used in the study is an index that shows the percentage distribution of women and men in each group studied. The results show that, despite the great progress experienced, much remains to be done.